Aspectos biológicos do desenvolvimento pré- implantacional de embriões bovinos partenogenéticos ou fecundados in vitro - Miyauchi, Tochimara Aparecida (2012)
Parthenogenesis has been described as an alternative method to produce embryos for studies with embryonic cells, particularly in humans which have a restriction of fertilized embryos. Procedures used in parthenogenesis are also required to produce embryos by somatic cell nuclear transfer in domestic species. However, many biological, cellular and molecular aspects of parthenogenetic embryos are still unknown. This study aimed to compare the kinetics of development, apoptosis rate and gene expression of stress and celular metabolism in bovine parthenogenetic embryos and embryos fertilized in vitro. Oocytes (n = 1541) obtained from slaughterhouse ovaries were matured in vitro and submitted to parthenogenetic activation (4.62 µM ionomycin for 5 min followed by 2 mM 6-DMAP for 4 h) or in vitro fertilization (2 x 106 sperm/mL for 20h with semen from a single departure). 72h postactivation/fertilization (hpaf), embryos (8-cell) were frozen for subsequent analysis of gene expression and another part has been separated into groups of high or low potential of development: Part ≥ 8 - parthenogenetic embryos with 8 or more cells (high development potential); Part < 8 - embryos less than 8 cells (low development potential); ≥ 8 IVF - in vitro fertilized embryos with 8 or more cells; and IVF < 8 - embryos with less than 8 cells. Embryos were cultured in CR2aa medium with 2.5% BFS in 5% CO2, 5% O2, 90% N2 at 38.5° C and were evaluated rates of blastocyst 168hpaf (D7) and 196hpaf (D8). 8-cell embryos obtained after 72hpfa were analyzed for gene expression. D8 blastocysts were fixed and subsequently apoptotic index was analyzed by TUNEL. Data were compared by analysis of variance and means by Student Newman Keuls test. Gene expression was evaluated by REST® software. Values are shown as mean ± standard error. Embryos with 8 or more cells produced higher (P < 0.01) blastocysts rates in D7 and D8 compared to embryos with less than eight cells, showing its greatest development potential, regardless if they were parthenogenetic or fertilized. Embryos of Part ≥ 8 group had higher (P <0.05) blastocyst rate in D7 (63.6 ± 3.4%) than IVF ≥ 8 (45.3 ± 8.9%), but at D8 rate was similar (56.7 ± 3.0% and 44.2 ± 8.9% for Part ≥ 8 and IVF ≥ 8, respectively; P <0.05). There was no difference (P < 0.05) on blastocyst rates at D7 and D8 between embryos with less than 8 cells derived from parthenogenesis or fertilization. There was no difference in total cell number (92.0 ± 3.4, 102.30 ± 4.8), apoptotic cells (10.8 ± 1.22, 9.5 ± 1.07) and apoptotic index (11.4 ± 1.27, 9.8 ± 1.8) for parthenogenetic and IVF blastocysts, respectively. In 8-cell embryos analyzed, there was a subexpression of genes DNAJB1, HSPA1L, HSF1 and GLUT1 for Part in relation to FIV, while HSF2 was overexpressed in Part compared to FIV. In conclusion, bovine parthenogenetic embryos differ to embryos fertilized in vitro in hability of preimplantation development in vitro and gene expression, which may limit the use of parthenogenesis in studies of embryonic development.